Quaternized polycyclic aromatic compounds for use in electrochemical devices - Patent Application 20070123633
Aryl ether-free polycyclic aromatic polymers with random copolymer structures and enhanced mechanical properties address the limitations of existing polymers, providing improved performance as ion exchange membranes in alkaline electrochemical devices.
Patent Information
- Application Number
- JP2025504031
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-05-17
- Filing Date
- 2023-02-06
- Publication Date
- 2025-04-10
AI Technical Summary
Aryl ether-free quaternized polycyclic aromatic polymers used in electrochemical devices face limitations due to insufficient mechanical properties, leading to issues like membrane thinning and pinhole formation under oxidative conditions.
Development of aryl ether-free polycyclic aromatic polymers based on random copolymer structures with two or more aromatic ring components, which are crosslinked and functionalized with multiple cationic groups to enhance mechanical properties and ion exchange capacity.
The resulting polymers exhibit improved mechanical stresses, ion exchange capacity, and hydroxide conductivity, making them suitable for use as ion exchange membranes in alkaline electrochemical devices, particularly in harsh operating conditions.
Smart Images

Figure 2025509002000001_ABST
Abstract
Description
[Background technology]
[0001] Fuel cells, water electrolyzers, and flow batteries are important chemical energy conversion devices for sustainable and renewable energy infrastructure. Polymer electrolytes function as ion exchange membranes in these electrochemical devices.
[0002] Aryl ether-free polyaromatic compounds are promising polymer electrolytes that can be used as stable membranes for electrochemical devices because aryl ether groups are not chemically stable under high pH conditions. Currently developed aryl ether-free quaternized polyaromatic electrolytes have limited mechanical properties that may lead to membrane defects such as membrane thinning and pinhole formation when exposed to the highly oxidative operating conditions of electrochemical devices. The issues associated with the poor mechanical properties of aryl ether-free quaternized polyaromatic compounds have been addressed by several methods, such as the synthesis of higher molecular weight polymers and reinforcement. The synthesis process of higher molecular weight polymers often requires higher polymerization temperatures and / or longer reaction times, which increase the chances of side reactions occurring. Although the reinforcement method shows a significant improvement in the tensile strength of the polymer, it requires additional processing to obtain a polymer electrolyte membrane and does not allow follow-up functionalization or further fabrication. Summary of the Invention [Means for solving the problem]
[0003] The present disclosure provides aryl ether-free polyaromatic polymers based on random copolymer structures with two, three, or more aromatic ring components, and their preparation. In some embodiments, the copolymers are crosslinked to enhance mechanical properties. In some embodiments, the polymers are functionalized with multiple cationic groups to increase ion exchange capacity. The polymers of the present disclosure can be used as ion exchange membranes, for example, as anion exchange membranes in alkaline electrochemical devices.
[0004] The present disclosure provides copolymers of Formula I: [ka] (However, Ar 1 , Ar 2 , Ar 3 , … and Ar n are different aryl groups to form a random copolymer, and n is from 2 to 20; a 1 , a 2 , a 3 , … and a n each of which is independently 1 to 1,000,000; R 1 , R 2 , R 3 , … and R n teeth, [ka] or a combination of these (where A is S, O, NH, SO 2 , alkyl groups (e.g., CH 2 or CH 2 CH 3 ), or a combination thereof, A' comprises N, an alkyl group, or a combination thereof, X comprises a halide (e.g., Br), FG comprises NR 3 + X - , N.R. 3 + OH - , O.H., N.R. 2 , S.O. 3 H, P(=O)(OH) 2 , CO 2 H, SO 3 - M + , P(=O)(O - ) 2 2M + , CO 2 - M +(M=Li, Na, K), linear multiple quaternary ammonium groups, branched multiple quaternary ammonium groups, bridged multiple quaternary ammonium groups, or combinations thereof; FG′ is NR 2 + X - or NR 2 + OH - R is an alkyl group (e.g., CH 3 or CH 2 CH 3 ) where x is 0 to 20 and y is 0 to 20.
[0005] In some embodiments, Ar 1 , Ar 2 , Ar 3 , … and Ar n teeth, [ka] or a combination thereof, where R is an alkyl group (e.g., CH 3 or CH 2 CH 3 ), halide (e.g., F), or combinations thereof, and R' is H, an alkyl group (e.g., CH 3 or CH 2 CH 3 ), or a combination thereof, where X comprises a halide, and A comprises S, O, NH, SO 2 , alkyl groups (e.g., CH 2 or CH 2 CH 3 ), or combinations thereof, where x is 0 to 20.
[0006] In some embodiments, R 1 , R 2 , R 3 , … and R n teeth, [ka] NHR 2, N,N,N',N'-tetramethyl-1,6-hexanediamine, bis(2-dimethylaminoethyl) ether, diamines, multiamines, or combinations thereof (wherein R is H, an alkyl group (e.g., CH 3 or CH 2 CH 3 ), or a combination thereof, where x is 0 to 20. In some embodiments, the copolymer has a degree of crosslinking of 0% to 100%, or any subrange therebetween.
[0007] In some embodiments, the copolymers have an ion exchange capacity (IEC) of about 0.5 to about 5.0 milliequivalents / gram. In some embodiments, the copolymers provided herein are used as ionomer binders or membranes in electrochemical devices.
[0008] In various embodiments, the copolymer is a random copolymer, and provided herein is an ion exchange membrane comprising the random copolymer. In some embodiments, the ion exchange membrane has a mechanical stress of greater than 30 MPa at about 50° C. and about 50% relative humidity. In some embodiments, the counter anion is chloride. In some embodiments, the random copolymer has a linear swelling ratio of about 10% to about 50% with hydroxide counter anion at 20° C. in deionized water. In some embodiments, the random copolymer has a hydroxide conductivity of greater than 80 mS / cm in deionized water at 80° C. In some embodiments, provided herein is a fuel cell comprising the ion exchange membrane.
[0009] In some embodiments, a random copolymer is provided having Formula II: [ka] (However, Ar 1 and Ar 2are different aryl groups, and each of m and n is independently 1 to 1,000,000. In various embodiments, Ar 1 and Ar 2 is, independently, [ka] or a combination thereof, where R is an alkyl group (e.g., CH 3 or CH 2 CH 3 ), halide (e.g., F), or combinations thereof, and R' is H, an alkyl group (e.g., CH 3 or CH 2 CH 3 ), or a combination thereof, where X comprises a halide, and A comprises S, O, NH, SO 2 , alkyl groups (e.g., CH 2 or CH 2 CH 3 ), or combinations thereof, wherein x is 0 to 20.
[0010] In some embodiments, the ammonium group side chain of the random copolymer of formula II is [ka] NR 3 , N,N,N',N'-tetramethyl-1,6-hexanediamine, bis(2-dimethylaminoethyl) ether, diamines, multiamines, or combinations thereof (wherein R is H, an alkyl group (e.g., CH 3 or CH 2 CH 3 ), or a combination thereof, where x is 0 to 20. In some embodiments, the degree of crosslinking is 0% to 100%. In some embodiments, the random copolymer has an ion exchange capacity (IEC) of about 0.5 to about 5.0 milliequivalents per gram (meq / g). The terms meq / g and meq / g are used interchangeably herein.
[0011] In some embodiments, provided herein is an ion exchange membrane comprising a random copolymer of formula II. In some embodiments, the ion exchange membrane has a mechanical stress of greater than 33 MPa at 50° C. and 50% relative humidity. In some embodiments, the counter anion is chloride. In some embodiments, the ion exchange membrane has a linear swelling ratio of 10% to 50% with hydroxide counter anion in deionized water at 20° C. In some embodiments, the ion exchange membrane has a hydroxide conductivity of greater than 80 mS / cm in deionized water at 80° C. In some embodiments, the ion exchange membrane comprises a crosslinked random copolymer. In some embodiments, the ion exchange membrane of the crosslinked random copolymer has a mechanical stress of greater than 35 MPa at 50° C. and 50% relative humidity. In some embodiments, the counter ion is chloride. In some embodiments, the ion exchange membrane has a linear swelling ratio of 10% to 50% with hydroxide counter anion in deionized water at 20° C. In some embodiments, the ion exchange membrane has a hydroxide conductivity in deionized water at 80° C. greater than 80 mS / cm.
[0012] In some embodiments, provided herein are random copolymers of Formula III: [ka] (wherein each of m and n is independently 1 to 1,000,000.) In some embodiments, the ratio of m to n is about 1:4 to about 4:1, or any subrange therebetween. In some embodiments, the random copolymer has an ion exchange capacity (IEC) of about 0.5 to about 5.0 milliequivalents per gram. In some embodiments, provided herein is an ion exchange membrane comprising the random copolymer of formula III. In some embodiments, provided herein is an alkaline electrochemical device comprising the random copolymer of formula III.
[0013] In some embodiments, provided herein are random copolymers according to Formula IV below: [ka] (wherein a, b, c, and d are each independently 1 to 1,000,000.) In some embodiments, the ratio of a to c is about 1:4 to about 4:1, or any subrange therebetween. In some embodiments, the random copolymer has an ion exchange capacity (IEC) of about 0.5 to about 5.0 milliequivalents per gram. In some embodiments, provided herein is an ion exchange membrane comprising the random copolymer of formula IV. In some embodiments, provided herein is an alkaline electrochemical device comprising the random copolymer of formula IV. As used in this disclosure, the term "random copolymer" refers to a statistical copolymer, i.e., one in which the sequence distribution of the monomers follows known statistical laws. [Brief description of the drawings]
[0014] [Figure 1] 1 shows the stress-strain curves of (a) 20% crosslinked BP-co-TPN1, (b) BP-co-TPN1, (c) TPN1, and (d) BPN1 at 50° C. and 50% relative humidity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present disclosure provides aryl ether-free polyaromatic polymers based on random copolymer structures with two, three, or more aromatic ring components. Some embodiments of the present disclosure are directed to electrochemical energy conversion systems, such as fuel cells, water electrolyzers, flow batteries, or combinations thereof. In some embodiments, the electrochemical energy conversion system includes at least one anode, at least one cathode, and one or more electrolytes in communication with the at least one anode and the at least one cathode. In some embodiments, the one or more electrolytes are disposed between the anode and the cathode. In some embodiments, the one or more electrolytes include a solid electrolyte. In some embodiments, the one or more electrolytes include a membrane, as discussed in more detail below.
[0016] In some embodiments, the polymer is one or more polymers including a polyaryl or polyaromatic backbone, where the polyaryl backbone is composed of two or more different aryl monomers. In some embodiments, the aryl monomer is a polyaryl monomer. In some embodiments, the polyaryl monomer includes a ring structure with more than one ring, two rings, three rings, four rings, five rings, or combinations thereof. Copolymers formed from two or more different randomized aromatic monomers unexpectedly exhibit higher tensile strength compared to their homopolymer counterparts with similar molecular weight. Without wishing to be bound by theory, this increased tensile strength may be due to the heterogeneity of the backbone structure resulting in a higher degree of chain entanglement.
[0017] In some embodiments, the monomer is, for example, [ka] or a combination thereof, where R is an alkyl group (e.g., CH 3 ), halide (e.g., F), or combinations thereof, and R' is H, an alkyl group (e.g., CH 3), or a combination thereof, where X comprises a halide, and A comprises S, O, NH, SO 2 , alkyl groups (e.g., CH 2 ), or combinations thereof, where x is from about 0 to about 20.
[0018] In some embodiments, the polymer is functionalized with one or more side chains. In some embodiments, the one or more side chains are functionalized with one or more alkyl groups, e.g., CH 3 , cycloalkyl groups, phenyl groups, halide groups, hydroxy groups, ammonium groups, linear multiple quaternary ammonium groups, branched multiple quaternary ammonium groups, bridged multiple quaternary ammonium groups, sulfonic acid groups, phosphonic acid groups, carboxylate groups, amines, alcohols, or combinations thereof. In some embodiments, one or more of the side chains are substituted with one or more functional groups. In some embodiments, the functional group is one or more alkyl groups, e.g., CH 3 , cycloalkyl groups, phenyl groups, halide groups, hydroxy groups, ammonium groups, linear multiple quaternary ammonium groups, branched multiple quaternary ammonium groups, bridged multiple quaternary ammonium groups, sulfonic acid groups, phosphonic acid groups, carboxylate groups, amines, alcohols, or combinations thereof. In some embodiments, one or more of the side chains are saturated, partially saturated, or combinations thereof.
[0019] In some embodiments, the polymer comprises Formula I: [ka] In some embodiments, Ar 1 , Ar 2 , Ar 3 , … and Ar n comprises a polyaryl group. In some embodiments, Ar 1 , Ar 2 , Ar 3 , … and Ar nIn some embodiments, the copolymer of formula I is a random copolymer formed from two or more different aromatic monomers. 1 , Ar 2 , Ar 3 , … and Ar n teeth, [ka] or a combination thereof, where R is an alkyl group (e.g., CH 3 ), halide (e.g., F), or combinations thereof, and R' is H, an alkyl group (e.g., CH 3 ), or a combination thereof, where X comprises a halide, and A comprises S, O, NH, SO 2 , alkyl groups (e.g., CH 2 ), or combinations thereof, where x is 0 to 20. 1 +a 2 +a 3 +…+a n is between 10 and 1,000,000. In some embodiments, R 1 , R 2 , R 3 , … and R n teeth, [ka] or a combination of these (where A is S, O, NH, SO 2 , an alkyl group, or a combination thereof; A' comprises N, an alkyl group, or a combination thereof; X comprises a halide (e.g., Br); FG comprises NR 3 + X - , N.R. 3 + OH - , O.H., N.R. 2 , S.O. 3 H, P(=O)(OH) 2 , CO 2 H, SO 3 - M +, P(=O)(O - ) 2 2M + , CO 2 - M + (M=Li, Na, K), linear multiple quaternary ammonium groups, branched multiple quaternary ammonium groups, bridged multiple quaternary ammonium groups, or combinations thereof; FG′ is NR 2 + X - , N.R. 2 + OH - R is an alkyl group (e.g., CH 3 or CH 2 CH 3 ) where x is 0 to 20 and y is 0 to 20.
[0020] In some embodiments, one or more of the above polymers are crosslinked to improve mechanical properties, including tensile strength, by the addition of a crosslinking agent. In some embodiments, the crosslinking agent is [ka] NR 3 , N,N,N',N'-tetramethyl-1,6-hexanediamine, bis(2-dimethylaminoethyl) ether, diamines, multiamines, or combinations thereof (wherein R is H, an alkyl group (e.g., CH 3 or CH 2 CH 3 ), or a combination thereof, where x is 0 to 20. ) In some embodiments, the degree of crosslinking is 0% to 100%.
[0021] In some embodiments, the copolymer has an ion exchange capacity (IEC) of 0.5 to 5.0 meq / g. In some embodiments, the copolymer comprises Formula II: [ka] Ar 1 and Ar 2are different aryl groups to form a random copolymer. In some embodiments, Ar 1 and Ar 2 comprises biphenyl, meta or para terphenyl, or a combination thereof. Each of m and n is independently 1 to 1,000,000. The IEC is varied by controlling the ratio of m and n. In some embodiments, the IEC is varied by controlling the degree of functionalization of the copolymer.
[0022] In some embodiments, the copolymer comprises Formula III: [ka] In some embodiments, the copolymer is a random copolymer. In some embodiments, the ratio of m to n is from about 1:4 to about 4:1, or any subrange therebetween. Each of m and n is independently from 1 to 1,000,000.
[0023] In some embodiments, the copolymer comprises Formula IV: [ka]
[0024] The copolymer of formula IV is a random copolymer. In some embodiments, the ratio of a to c is from about 1:4 to about 4:1, or any subrange therebetween. Each of a, b, c, and d is independently from 1 to 1,000,000. In some embodiments, the IEC varies with the ratio of b and d. In some embodiments, the IEC of the copolymer is from 0.5 to 5.0 milliequivalents / g.
[0025] In some embodiments, one or more of the above polymers form a membrane, for example, an ion exchange membrane. In some embodiments, the membrane has a thickness of about 5 microns to about 300 microns. Thinner membranes, for example, 5 to 50 microns, exhibit lower resistance and lower mechanical properties. Thicker membranes, for example, greater than 75 microns, exhibit higher resistance and higher mechanical properties.
[0026] In some embodiments, the membranes include one or more dopants. In some embodiments, the one or more dopants include phosphoric acid-based proton conductors, and the like. In some embodiments, the polymers are utilized in electrochemical devices as quaternary ammonium-phosphonate ion-pair coordinated proton conducting membranes. In some embodiments, the polymers are utilized as membranes capable of operating at high temperature and low relative humidity conditions. In some embodiments, the polymers are utilized as membranes capable of operating at temperatures above about 80° C. In some embodiments, the polymers are incorporated, for example as components of membranes, into high temperature proton exchange membrane fuel cells, steam electrolyzers, and the like, while the anion exchange membranes in alkaline electrochemical devices are utilized in low temperature fuel cells, low temperature water electrolyzers, CO 2 These include electrolysers, electrochemical compressors, redox flow batteries, electrodialysis, reverse electrodialysis where the diffusion of anions is important, etc., or combinations thereof.
[0027] The disclosed methods and systems are advantageous in that they provide a combination of monomers that form suitable backbone structures to obtain high mechanical strength polymers, including aryl ether-free quaternized polyaromatic rings produced by copolymerization of different aromatic ring structures.
[0028] The synthesis of polyaromatic electrolytes based on homopolymers has been reported, for example, in WO 2016 / 081432. The polymerization step is carried out by acid-catalyzed Friedel-Crafts condensation polymerization, which is a promising method to form long chains of repeat units composed of one aromatic and one ketone monomer in one pot at room temperature. However, copolymers formed with two or three different aromatic monomers unexpectedly show higher tensile strength compared to their homopolymer counterparts with similar molecular weights. Without wishing to be bound by theory, this increase in tensile strength may be due to the heterogeneity of the backbone structure leading to a higher degree of molecular chain entanglement.
[0029] By controlling the polymer backbone structure and their intertwined network structure, these polymers are advantageous for use in electrochemical devices, for example, as ion exchange membranes with good mechanical properties in devices that require harsh operating conditions for higher performance. Controlling the composition of aromatic ring structures in the copolymers allows for high mechanical strength that can improve device performance and durability.
[0030] While the present invention has been described and illustrated with respect to exemplary embodiments thereof, it will be understood by those skilled in the art that modifications, omissions, and additions may be made within and to the invention, as discussed above, and in various other ways, without departing from the spirit and scope of the invention.
[0031] (Example) Example 1: BP-co-TPN1 Precursor The BP-co-TPN1 precursor copolymer was synthesized by the superacid-catalyzed reaction of functionalized trifluoromethyl alkyl ketones with two aromatic hydrocarbons, e.g., biphenyl and m-terphenyl, as previously reported (Zolotukin, M. et al., Macromolecules 2013, 46, 7245). [ka]
[0032] Polymer synthesis was carried out at room temperature. A mixture of 7-bromo-1,1,1-trifluoroheptan-2-one (32 g, 130 mmol), biphenyl and m-terphenyl (10 g, 65 mmol, and 15 g, 65 mmol, respectively), methylene chloride (200 mL), and triflic acid (84 mL) was stirred at room temperature for 12 h and then poured into methanol. The copolymer was filtered and washed with methanol. After drying, 54 g of fibrous precursor polymer was obtained (99%).
[0033] Example 2: BP-co-TPN1 BP-co-TPN1 was synthesized by quaternization of the alkyl bromide groups of the BP-co-TPN1 precursor, which is a common method for the preparation of anion exchange membranes. A mixture of BP-co-TPN1 precursor (50 g, 119 mmol), trimethylamine (31.2 g, 238 mmol), and a good solvent (DMF, DMAc, NMP, DMSO, etc.) was stirred at room temperature for 24 h and then poured into a poor solvent. The product was filtered and washed with the poor solvent. [ka]
[0034] Table 1 below summarizes the mechanical properties of homopolymers (e.g., BPN1 and TPN1), copolymers (e.g., BP-co-TPN1 and 20% crosslinked copolymer). BP-co-TPN1 exhibited an unexpectedly high mechanical stress of 40 MPa compared to the homopolymers BPN1 or TPN1, but its elongation at break and hydroxide conductivity were in a similar range. Crosslinking 20% of BP-co-TPN1 with N,N,N',N'-tetramethyl-1,6-hexanediamine further improved the mechanical strength to 45 MPa.
[0035] Table 1: Mechanical properties and hydroxide conductivity of homopolymers and random copolymers. [Table 1]
[0036] FIG. 1 shows the stress-strain curves of (a) 20% crosslinked BP-co-TPN1, (b) BP-co-TPN1, and (c) TPN1 and (d) BPN1 with chloride counteranion at 50° C. and 50% relative humidity. The copolymer (b) BP-co-TPN1 exhibited an unexpectedly higher mechanical stress than that of the homopolymers (c) TPN1 or (d) BPN1. (a) BP-co-TPN1 crosslinked 20% with N,N,N′,N′-tetramethyl-1,6-hexanediamine exhibited a higher mechanical stress than that of (b) BP-co-TPN1.
[0037] Table 2 below shows the anion exchange membrane properties, such as water content, hydroxide conductivity, and mechanical properties, of 20% crosslinked BP-co-TPN1 with different IECs of 2.2, 2.4, 2.8, and 3.1 meq / g. All of the copolymers with different IECs from 2.2 to 3.1 meq / g showed very good ionic conductivity and mechanical properties. The polymer electrolytes with the same backbone chemical structure with different IECs give users more options to choose the right polymer electrolyte according to their applications.
[0038] Table 2: Water content, hydroxide conductivity, and mechanical properties of 20% crosslinked BP-co-TPN1 with various ion exchange capacities. [Table 2]
[0039] [Note] [Appendix 1] A copolymer of formula I below. [ka] (However, Ar 1 , Ar 2 , Ar 3 , … and Ar n are different aryl groups to form a random copolymer, a 1 , a 2 , a 3 , … and a n each of which is independently 1 to 1,000,000; R 1 , R 2 , R 3 , … and R n Each of the following is independently [ka] and combinations thereof (wherein A is S, O, NH, SO 2 , alkyl groups (e.g., CH 2 or CH 2 CH 3 ), or a combination thereof, A' includes N, an alkyl group, or a combination thereof, X is a halide (e.g., Br), and FG is NR 3 + X - , N.R. 3 + OH - , O.H., N.R. 2 , S.O. 3 H, P(=O)(OH) 2 , CO 2 H, SO 3 - M + , P(=O)(O - ) 2 2M + , CO 2 - M + (M=Li, Na, K), linear multiple quaternary ammonium groups, branched multiple quaternary ammonium groups, bridged multiple quaternary ammonium groups, or combinations thereof; FG′ is NR 2 + X - or NR 2 + OH - R is an alkyl group (e.g., CH 3 or CH 2 CH 3) wherein x is 0 to 20 and y is 0 to 20.
[0040] [Appendix 2] Ar 1 , Ar 2 , Ar 3 , … and Ar n Each of the following is independently [ka] and combinations thereof, provided that R is an alkyl group (e.g., CH 3 or CH 2 CH 3 ), halide (e.g., F), or combinations thereof, and R' is H, an alkyl group (e.g., CH 3 or CH 2 CH 3 ), or a combination thereof, where X comprises a halide, and A comprises S, O, NH, SO 2 , alkyl groups (e.g., CH 2 or CH 2 CH 3 2. The copolymer of claim 1, selected from:
[0041] [Appendix 3] R 1 , R 2 , R 3 , … and R n teeth, [ka] NHR 2 , N,N,N',N'-tetramethyl-1,6-hexanediamine, bis(2-dimethylaminoethyl) ether, diamines, multiamines, or combinations thereof (wherein R is H, an alkyl group (e.g., CH 3 or CH 2 CH 3) or a combination thereof, wherein x is 0 to 20.
[0042] [Appendix 4] 4. The copolymer of claim 3, having a degree of crosslinking of 0% to 100%.
[0043] [Appendix 5] The copolymer of claim 1, wherein the copolymer has an ion exchange capacity (IEC) of about 0.5 to about 5.0 milliequivalents / g.
[0044] [Appendix 6] 2. An electrochemical device comprising a hydrocarbon-based polymer film comprising the copolymer of claim 1.
[0045] [Appendix 7] A copolymer as described in Appendix 1, having the following formula II: [ka] (However, Ar 1 and Ar 2 are different aryl groups, and each of m and n is independently 1 to 1,000,000.
[0046] [Appendix 8] A copolymer as described in Appendix 1, having the following formula III: [ka] wherein each of m and n is independently 1 to 1,000,000.
[0047] [Appendix 9] A copolymer according to claim 7, having the following formula IV: [ka] wherein a, b, c, and d are each independently 1 to 1,000,000; Biphenyl and m-terphenyl are not directly connected, CF 3 C(CH 2 ) 5 N + (CH 3 ) 3 (OH - ) and CF 3 C(CH 2 ) 5 N + (CH 3 ) 2 (OH - )(CH 2 ) 6 N + (CH 3 ) 3 (OH - ) are not directly connected.
[0048] [Appendix 10] An ion exchange membrane comprising the copolymer described in appended claim 1.
[0049] [Appendix 11] 11. The ion exchange membrane of claim 10, wherein the ion exchange membrane has a mechanical stress of greater than 30 MPa at about 50° C. and about 50% relative humidity.
[0050] [Appendix 12] 11. The ion exchange membrane of claim 10 having a halide counter anion.
[0051] [Appendix 13] 11. The ion exchange membrane of claim 10, wherein the copolymer has a linear swelling ratio of about 10% to about 50% with hydroxide counteranion in deionized water at 20° C.
[0052] [Appendix 14] 11. The ion exchange membrane of claim 10, having a hydroxide conductivity of greater than 80 mS / cm in deionized water at 80° C.
[0053] [Appendix 15] 9. An ion exchange membrane comprising the copolymer described in claim 8.
[0054] [Appendix 16] 10. An ion exchange membrane comprising the copolymer of claim 9.
[0055] [Appendix 17] 17. The ion exchange membrane of claim 16, wherein the random copolymer has an ion exchange capacity (IEC) of about 0.5 to about 5.0 milliequivalents / g.
[0056] [Appendix 18] An ion exchange membrane comprising the copolymer of claim 1 and one or more dopants.
[0057] [Appendix 19] 19. The ion exchange membrane of claim 18, wherein the one or more dopants include a phosphoric acid-based proton conductor.
[0058] [Appendix 20] 19. An electrochemical device comprising the ion exchange membrane of claim 18, having the ability to operate at a temperature greater than about 80° C.
Claims
1. A copolymer of formula I below. 【Chemistry 1】 (However, Ar 1 , Ar 2 , Ar 3 , … and Ar n are different aryl groups to form a random copolymer, a 1 , a 2 , a 3 , ... and a n each is independently 1 to 1,000,000; R 1 , R 2 , R 3 , … and R n Each of the following is independently 【Chemistry 2】 and the group consisting of combinations thereof (wherein A is S, O, NH, SO 2 , alkyl group (e.g., CH 2 or CH 2 CH 3 ), or a combination thereof, A′ includes N, an alkyl group, or a combination thereof, X is a halide (e.g., Br), and FG is NR 3 + X - , N.R. 3 + O.H. - , O.H., N.R. 2 , S.O. 3 H, P (=O) (OH) 2 , CO 2 H, SO 3 - M + , P(=O)(O - ) 2 2M + , CO 2 - M + (M=Li, Na, K), linear multiple quaternary ammonium groups, branched multiple quaternary ammonium groups, bridged multiple quaternary ammonium groups, or combinations thereof; FG′ is NR 2 + X - Or N.R. 2 + O.H. - R is an alkyl group (e.g., CH 3 or CH 2 CH 3 ) wherein x is 0 to 20 and y is 0 to 20.
2. Ar 1 , Ar 2 , Ar 3 , … and Ar n Each of the following is independently 【Chemistry 3】 and combinations thereof, provided that R is an alkyl group (e.g., CH 3 or CH 2 CH 3 ), halide (e.g., F), or combinations thereof, and R′ is H, an alkyl group (e.g., CH 3 or CH 2 CH 3 ), or a combination thereof, where X comprises a halide, and A comprises S, O, NH, SO 2 , alkyl group (e.g., CH 2 or CH 2 CH 3 2. The copolymer of claim 1 , wherein the copolymer is selected from:
3. R 1 , R 2 , R 3 , … and R n teeth, 【Chemistry 4】 NHR 2 , N,N,N',N'-tetramethyl-1,6-hexanediamine, bis(2-dimethylaminoethyl)ether, diamines, multiamines, or combinations thereof (wherein R is H, an alkyl group (e.g., CH 3 or CH 2 CH 3 3. The copolymer of claim 2, which is crosslinked with a crosslinker selected from the group consisting of:
4. The copolymer of claim 3 having a degree of crosslinking of from 0% to 100%.
5. 10. The copolymer of claim 1, wherein the copolymer has an ion exchange capacity (IEC) of about 0.5 to about 5.0 meq / g.
6. 13. An electrochemical device comprising a hydrocarbon-based polymer membrane comprising the copolymer of claim 1.
7. 2. The copolymer of claim 1 having formula II: 【Chemistry 5】 (However, Ar 1 and Ar 2 are different aryl groups, and each of m and n is independently 1 to 1,000,000.
8. 2. The copolymer of claim 1 having formula III: 【Chemistry 6】 (wherein each of m and n is independently 1 to 1,000,000.)
9. 8. The copolymer of claim 7 having formula IV: 【Chemistry 7】 wherein a, b, c, and d are each independently 1 to 1,000,000; Biphenyl and m-terphenyl are not directly connected, CF 3 C (CH 2 ) 5 N + (CH 3 ) 3 (OH - ) and C.F. 3 C (CH 2 ) 5 N + (CH 3 ) 2 (OH - ) (CH 2 ) 6 N + (CH 3 ) 3 (OH - ) are not directly connected.
10. An ion exchange membrane comprising the copolymer of claim 1.
11. 11. The ion exchange membrane of claim 10, wherein the ion exchange membrane has a mechanical stress of greater than 30 MPa at about 50°C and about 50% relative humidity.
12. The ion exchange membrane of claim 10 having a halide counteranion.
13. 11. The ion exchange membrane of claim 10, wherein the copolymer has a linear swelling ratio of about 10% to about 50% with hydroxide counteranion in deionized water at 20°C.
14. 11. The ion exchange membrane of claim 10 having a hydroxide conductivity of greater than 80 mS / cm in deionized water at 80°C.
15. An ion exchange membrane comprising the copolymer of claim 8.
16. An ion exchange membrane comprising the copolymer of claim 9.
17. 17. The ion exchange membrane of claim 16, wherein the random copolymer has an ion exchange capacity (IEC) of about 0.5 to about 5.0 meq / g.
18. An ion exchange membrane comprising the copolymer of claim 1 and one or more dopants.
19. 20. The ion exchange membrane of claim 18, wherein the one or more dopants comprise a phosphoric acid-based proton conductor.
20. 20. An electrochemical device comprising the ion exchange membrane of claim 18 having the capability of operating at temperatures greater than about 80°C.
Citation Information
Patent Citations
Cation group-containing ether bond-free polyfluorene alkylene, preparation method thereof and anion exchange membrane
CN109320692A
Polyelectrolyte material, preparation method thereof and alkaline polyelectrolyte membrane
CN112940226A
Resin substrate for circuit board, resin composition for circuit board, and circuit board
JP2016032098A
Crosslinking of polymers for anion exchange membranes
JP2021523978A
Proton exchange membrane fuel cells
US10622657B1